The efficiency of trading halts: emerging market evidence - Bacha, Obiyathulla Ismath; A. Rashid, Mohamed Eskandar S; Ramlee, Roslily (Universiti Utara Malaysia Pres, 2008)
This paper reports new findings on the price effect from trading halts - both voluntary and mandatory - over 2000-2004 in an emerging share market, Malaysia. Based on our overall sample, trading halts lead to positive price reaction, increased volume, and increased volatility. We found evidence of information leakage resulting in a significant difference between voluntary and mandatory halts as well as the type of news released during halts to warrant such an impact. The duration of the halt has an isolated impact and is largely inconsequential. The frequency of halts does not seem to matter